Evaluation of Reading Interest Based on Octalysis Gamification - Fairuzabadi, Ahmad; Rahman, Afida (Journal of Information Technology application in Education, Economy, Health and Agriculture, 2024)
An abstract is often presented separate from the article, so it must be able to In the rapidly evolving information and technology era, literacy remains a crucial factor for a competitive and innovative society. Despite its significance, Indonesia faces a severe literacy challenge, evidenced by low reading interest and poor performance in international assessments like PISA. This issue is exacerbated by data from UNESCO and global literacy rankings, revealing that only a minimal fraction of the population engages in regular reading. With the advent of Industry 4.0, the ability to access and analyze information through reading has become increasingly vital. This study aims to address this challenge by leveraging gamification to enhance reading motivation and engagement. Specifically, it employs the Octalysis Framework by Yu-kai Chou to design a gamified system tailored to intrinsic user motivations. The research has three main objectives: identifying user profiles using Octalysis to understand individual reading motivations; designing and implementing gamification elements in the "Codex Horizon" app, including points, achievements, and community features; and evaluating the effectiveness of these elements in increasing reading engagement. The study seeks to provide insights into how gamification, grounded in Octalysis Framework, can be utilized to improve literacy in Indonesia, offering practical guidance for developers, educators, and policymakers.